The 2003 U.S. Dividend Tax Cut, Small Business Loan Supply, and the Real Economy - Li, Oliver Zhen; Lin, Yupeng; Zhang, Keyuan (The Accounting Review, 2026)
ABSTRACT This paper examines the credit supply-side effect of the U.S. 2003 dividend tax cut on the real economy through the banking sector. We show that C-corporation banks (treatment group), particularly those capital-constrained, increase the supply of small business loans more than S-subchapter banks (control group) following the tax cut, aligning with the old view of dividend taxation and the supply-side effect rooted in credit rationing. Such an enhanced small business loan supply stemming from the tax cut translates into real effects on the economy. We find that areas with a greater presence of C-corporation banks exhibit more small business formations, employment, and innovations. The positive real effects are concentrated in subsamples when business growth opportunities are more abundant or international trade exposures are higher. Overall, our findings add to the literature on the real effects of the tax cut by showing an important yet unexplored bank credit supply channel.